Transarterial chemoembolization combined with metformin improves the prognosis of hepatocellular carcinoma patients with type 2 diabetes - Chen, Miao-Ling; Wu, Chun-Xue; Zhang, Jian-Bo; Zhang, Hao; Sun, Yuan-Dong; Tian, Shi-Lin; Han, Jian-Jun (Frontiers in Endocrinology, 2022)
Abstract Objective: The study aims to investigate the effect of metformin on Hepatocellular carcinoma (HCC) patients with type 2 diabetes mellitus (T2DM) who received transarterial chemoembolization (TACE) for the first time. Methods: From January 2016 to December 2019, T2DM patients diagnosed with HCC in Shandong Cancer Hospital and treated with TACE were included in this retrospective study. Overall survival (OS) and Progression-free survival (PFS) were compared between patients treated with metformin and other antidiabetics. Univariate and multivariate Cox regression models were used to evaluate the independent risk factors associated with OS and PFS. And sub-analysis was performed to investigate whether metformin could give a survival advantage in each Barcelona Clinic Liver Cancer (BCLC) stage of HCC. Propensity score matched (PSM) analyses based on patient and tumor characteristics were also conducted. Results: A total of 123 HCC patients with T2DM underwent TACE, of which 50 (40.65%) received treatment with metformin. For the whole cohort, the median OS (42 vs 32 months, p=0.054) and PFS (12 vs 7 months, P=0.0016) were longer in the metformin group than that in the non-metformin group. Multi-analysis revealed that BCLC stage, BMI (Body Mass Index), and metformin use were independent predictors of OS. Metformin use was independently associated with recurrence. After PSM, 39 matched pairs were identified. The use of metformin was associated with a numerically longer m OS (43 vs 35 months, P=0.183) than the use of other anti-diabetics. And the difference in median PFS (13 vs 7 months, p=0.018) between the metformin group and non-metformin group remained significant. Conclusion: The combination of transarterial chemoembolization and metformin may be associated with better OS and PFS in HCC patients with T2DM.